Wundersmith : the calling of Morrigan Crow - Townsend, Jessica, 1985- (Little, Brown and Company, 2018)
"Morrigan Crow is now a proud scholar in the elite Wundrous Society, but must prove that she belongs in the Society, while battling a new evil"--